INDIKASI TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ginting, Wenny Anggeresia; Hantono, Hantono; Susanto, Asen (KEUNIS, 2023)
Transfer pricing is a price transfer policy in a transaction carried out by a certain party and following the applicable laws and regulations. Many companies take advantage of this for other purposes, namely avoiding taxes. Tax evasion is a complicated matter and is an act that does not violate the law, but on the other hand, tax evasion is not accepted by the government because it can reduce the amount of income sourced from taxes. The type of research used in this research is explanatory research with a quantitative approach. The population in this study is all manufacturing companies in 2019-2021, with a total of 116 companies. Sampling was done by purposive sampling. The results of the simultaneous research of the three variables do not influence transfer tracing. While partially only the Tunneling Incentive variable (X2) has an effect, the Debt Covenant (X1) and Bonus Mechanism (X3) have no effect. For future researchers, adding other variables and expanding the research sample are suggested.